Model Age Derivation of Large Martian Impact Craters, Using Automatic Crater Counting Methods. Issue 2 (18th February 2021) - Lagain, A.; Servis, K.; Benedix, G. K.; Norman, C.; Anderson, S.; Bland, P. A.
Abstract: Determining when an impact crater formed is a complex and tedious task. However, this knowledge is crucial to understanding the geological history of planetary bodies and, more specifically, gives information on erosion rate measurements, meteorite ejection location, impact flux evolution and the loss of a magnetic field. The derivation of an individual crater's age is currently performed through manual counting. Because crater size scales as a power law, this method is limited to small (and/or young) surface areas and, in the case of the derivation of crater emplacement age, to a small set of impact craters. Here, we used a Crater Detection Algorithm, specifically retrained to detect small impact craters on large‐ and high‐resolution imagery data set to solve this issue. We applied it to a global, 5 m/pixel resolution mosaic of Mars. Here, we test the use of this data set to date 10 large impact craters. We developed a cluster analysis tool in order to distinguish potential secondary crater clusters from the primary crater population. We then use this, filtered, crater population to date each large impact crater and evaluate our results against literature ages. We found that automated counting filtered through clustering analysis produced similar model ages to manual counts. This technique can now be expanded to much wider crater dating surveys, and by extension to any other kind of Martian surface. We anticipate that this new tool will considerably expand our knowledge of the geological events that have shaped the surface of Mars, their timing and duration. Plain Language Summary: The age of an impact crater on a planetary surface is a crucial constraint in determining erosion rate, the crater source of Martian meteorites and the impact cratering flux evolution. This kind of measurement requires the counting of many impact craters superposed on the ejecta blanket of the considered crater and is therefore limited by human capability. To solve this issue, we adapted an automatic tool to detect small impact craters on the surface of Mars. We also developed an automatic approach to identify and remove clusters of small likely secondary craters detected by our algorithm. We assume these clusters of craters are formed by fragments ejected by an impact that formed a primary crater and need to be removed from crater densities used for age derivations. We applied our technique on 10 large Martian impact craters whose the formation age has been derived using manual counts and reported in the literature. We compared these ages to ours, derived from automatic count and automatic secondary craters filtering. Our results are consistent and indistinguishable from an age inferred from a manual count. For the first time, we demonstrate that an automated approach can deliver geologically meaningful model ages. Key Points: Automatic detection of small craters on ejecta blanket of 10 large Martian craters Identification of secondary craters through cluster analysis Model ages from our semi‐automatic approach are similar from manual counts